Co-electrolysis of simulated coke oven gas using solid oxide electrolysis technology. (1st December 2020) - Czachor, Michal; Laycock, Christian J.; Carr, Stephen J.W.; Maddy, Jon; Lloyd, Gareth; Guwy, Alan J.
Graphical abstract: Highlights: Solid oxide electrolysis of simulated coke oven gas with steam investigated. The hydrogen content was increased by 119% with a purity of 91.7% by volume. Worldwide, this could achieve a hydrogen production of up to 87.6 million tonnes. 89% of hydrogen production was via catalysis; 16% was by steam reduction. The high steam-to-carbon ratios used considerably alleviated carbon deposition. Abstract: Coke oven gas is a by-product of coke production for steelmaking and by volume typically consists of 55–60% hydrogen, 23–27% methane and impurities. An estimated 650 million tonnes of coke oven gas are produced worldwide, with up to 50% re-utilised within steelmaking. However, the rest is flared, contributing to carbon emissions and wasting valuable and useful gases. This study has investigated the co-electrolysis of simulated coke oven gas with steam using commercially available solid oxide electrolysis technology for the purposes of recovering hydrogen. The electrochemical performance of an anode supported button cell was characterised using open circuit potential measurements, current-voltage curves and electrochemical impedance spectroscopy. The product gas composition was analysed using quadrupole mass spectrometry. Co-electrolysis of simulated coke oven gas (30/70% methane/hydrogen) with 50% steam achieved a hydrogen amplification of 119% and a purity of 91.7% by volume, balanced mainly in carbon dioxide and carbon monoxide. Theoretically, this corresponds to a worldwide hydrogen production from coke oven gas of 87.6 million tonnes, which is in excess of the current global demand for hydrogen (70 million tonnes). Catalytic steam reforming of methane and the water-gas shift reaction increased the hydrogen content by 89% and a further 16% gain was due to electrochemical steam reduction. Co-electrolysing at high steam-to-carbon ratios was shown to increase hydrogen yield, improve cell performance, maximise methane and carbon monoxide conversion and inhibit carbon deposition. Studies into fuel variability effects show that greater methane contents gave higher hydrogen yields but decreased hydrogen purity and cell performance. Increasing the operating voltage increased the conversion of carbon dioxide into carbon monoxide via promotion of the reverse water-gas shift reaction. The work demonstrates the considerable potential to upgrade coke oven gas using solid oxide electrolysis technology, which could enable greater downstream recovery and purification of hydrogen from an under-utilised industrial waste resource.